Happiness and public policy - "Ng Yew-Kwang, (ed.)" (New York, 2006)
This volume discusses the determinants of happiness and presents case studies of how public policy can help promote happiness. Happiness is a private matter and individual pursuit, however public policy does have an important role and can contribute much through various enabling means. Possible examples of such influence include establishing a set of institutions that allow private enterprises to flourish, investing in infrastructure and in education, protecting people from harm and reducing risks and alleviating pain when harm is unavoidable. This book takes a multidisciplinary approach that encompasses economics, psychology, sociology, anthropology, political science and an international perspective.
Keywords: Public policy-Case studies